COMPARATIVE DETERMINATION AND HEALTH RISK ASSESSMENT OF CADMIUM, CHROMIUM AND COPPER IN WILD AND AQUACULTURED CLARIAS GARIEPINUS, OREOCHROMIS NILOTICUS AND MICROPOGONIAS UNDULATUS SOLD IN GWAGWALADA AREA COUNCIL, FCT - NIGERIA. - DALLATU, EPHRAIM; EMUROTU, JUDE E.; UGBEDEOJO, ATUMEYI A.; ESTHER, IBRAHIM; ONUGWU, ERNEST O. (Journal of the Chilean Chemical Society, 2024)
This study assesses the levels of copper (Cu), chromium (Cr), and cadmium (Cd) in wild and aquacultured Oreochromis niloticus (Tilapia), Micropogonias undulatus (Croaker), and Clarias gariepinus (Catfish) that are sold in Gwagwalada Area Council, Federal Capital Territory, Nigeria. A random sample of 500 g of each species of fish was taken from the markets in Dobi, Gwagwalada, and Zuba. The labels for the composite samples were: aquacultured catfish (Acf), aquacultured tilapia (Atf), aquacultured croaker (Acrf), wild catfish (Wcf), wild tilapia (Wtf), and wild croaker (Wcrf). Oven-dry weight and furnace procedures were used to determine the contents of moisture and ash. Wcf, Wtf, and Wcrf had moisture contents of 4.25±0.354%, 5.25±0.453%, and 4.50±0.000%, respectively, according to the results, whereas Acf, Atf, and Acrf had moisture contents of 7.01±0.230%, 7.12±0.234%, and 6.70±0.210%, respectively. For Wcf, Wtf, and Wcrf, the ash content was 1.75±0.354%, 1.64±0.231%, and 1.48±0.213%, respectively. The possible health concerns linked with the consumption of these heavy metals were determined by measuring and comparing their concentrations. The results show that various fish species accumulate metals at different rates, which could have an impact on public health because extended exposure to these toxins can cause health problems.